FACTORS AFFECTING FINANCIAL FRAUD OF INDONESIAN CONSTRUCTION COMPANIES USING FRAUD DIAMOND PERSPECTIVE - Ni Putu Gianitri Widyashanti (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study is conducted to analyse the factors affecting financial statement fraud in construction companies listed in the Indonesian Stock Exchange during the period of 2010-2014 using the four elements of the fraud diamond perspective by Wolfe and Hermanson (2004). There are 30 companies observed, examined through four independent variables such as, return on assets from financial target pressure, reception to industry opportunity, auditor change from auditor rationalization, and change in directors from management capability towards dependent variable, discretionary accruals from financial statement fraud. Hypothesis testing is carried using multiple linear regression.The analysis results showed that only industry opportunity which is proxied by reception had a significant effect in financial statement fraud. Meanwhile, the other three variables: pressure which is proxied by return on asset, rationalization which is proxied by change in auditor, and capability which is proxied by the change of directors, failed in showing significant effects against financial statement fraud. The insignificant factor of auditor and director change in detecting financial statement fraud might have occurred due to the incompetence of auditor and director themselves. Furthermore, since return the on assets is always used for short-term goals, this might be a reason behind financial target pressure failing to affect financial statement fraud. Keywords:       Fraud Diamond, Financial Statement Fraud, Earnings Management.